Nitrogen-Dependent Posttranscriptional Regulation of the Ammonium Transporter AtAMT1;1 - Yuan, Lixing (American Society of Plant Biologists, 2007)
Ammonium transporter (AMT) proteins of the AMT family mediate the transport of ammonium across plasma membranes. To investigate whether AMTs are regulated at the posttranscriptional level, a gene construct consisting of the cauliflower mosaic virus 35S promoter driving the Arabidopsis (Arabidopsis thaliana) AMT1;1 gene was introduced into tobacco (Nicotiana tabacum). Ectopic expression of AtAMT1;1 in transgenic tobacco lines led to high transcript levels and protein levels at the plasma membrane and translated into an approximately 30% increase in root uptake capacity for (15)N-labeled ammonium in hydroponically grown transgenic plants. When ammonium was supplied as the major nitrogen (N) form but at limiting amounts to soil-grown plants, transgenic lines overexpressing AtAMT1;1 did not show enhanced growth or N acquisition relative to wild-type plants. Surprisingly, steady-state transcript levels of AtAMT1;1 accumulated to higher levels in N-deficient roots and shoots of transgenic tobacco plants in spite of expression being controlled by the constitutive 35S promoter. Moreover, steady-state transcript levels were decreased after addition of ammonium or nitrate in N-deficient roots, suggesting a role for N availability in regulating AtAMT1;1 transcript abundance. Nitrogen deficiency-dependent accumulation of AtAMT1;1 mRNA was also observed in 35S:AtAMT1;1-transformed Arabidopsis shoots but not in roots. Evidence for a regulatory role of the 3′-untranslated region of AtAMT1;1 alone in N-dependent transcript accumulation was not found. However, transcript levels of AtAMT1;3 did not accumulate in a N-dependent manner, even though the same T-DNA insertion line atamt1;1-1 was used for 35S:AtAMT1;3 expression. These results show that the accumulation of AtAMT1;1 transcripts is regulated in a N- and organ-dependent manner and suggest mRNA turnover as an additional mechanism for the regulation of AtAMT1;1 in response to the N nutritional status of plants.